Optimizing HLA desensitization: serum dilution strategies and platform-specific MFI thresholds for antibody-mediated rejection risk in kidney transplantation - Bertrand, Dominique; Dard, Céline; Kaveri, Rangolie; Jouve, Thomas; Malvezzi, Paolo; Rostaing, Lionel; Guerrot, Dominique; Lemoine, Mathilde; Laurent, Charlotte; Noble, Johan; Farce, Fabienne (Frontiers in Immunology, 2025)
IntroductionHighly sensitized kidney transplant (KT) candidates are at increased risk of antibody-mediated rejection (ABMR), particularly in the context of desensitization protocols. Accurate quantification of donor-specific antibodies (DSA) using Luminex single antigen bead (SAB) assays remains essential but is limited by signal saturation and inter-platform variability.MethodsWe conducted a bicentric study involving 20 sensitized KT recipients undergoing HLA desensitization. Anti-HLA antibody profiles were analyzed using Immucor- Werfen (IM) and One Lambda-Thermofisher (OL) SAB platforms. Serum samples were tested both undiluted and at 1:10 dilution before and after desensitization.ResultsDiluted pre-desensitization sera showed stronger correlation with post-desensitization DSA levels than pure sera (R² > 0.90 for IM; > 0.85 for OL). The sum of the DSA (sDSA) outperformed immunodominant DSA (iDSA) in predicting early ABMR. ROC analysis revealed good predictive power (AUC 0.79– 0.88), with IM providing superior iDSA discrimination. For the first time, we propose IM-specific MFI thresholds relevant for ABMR risk stratification.DiscussionSerum dilution improves the clinical interpretation of DSA intensity and refines risk assessment in desensitized KT candidates. Our findings support the integration of platform-specific MFI cutoffs and dilution-based antibody profiling into organ acceptance strategies for highly sensitized patients.